The patterns of refractive errors among the school children of rural and urban settings in Nepal - Pokharel, A; Pokharel, PK; Das, H; Adhikari, S (Nepalese Journal of Ophthalmology, 2010)
Introduction: The uncorrected refractive error is an important cause of childhood blindness and visual impairment. Objective: To study the patterns of refractive errors among the urban and rural school going children of Nepal. Subjects and methods: A total of 440 school children of urban and rural schools within the age range of 7-15 years were selected for this study using multi-stage randomization technique. Results: The overall prevalance of refractive error in school children was 19.8 %. The commonest refractive error among the students was myopia (59.8 %), followed by hypermetropia (31.0 %). The children of age group 12-15 years had the higher prevalence of myopia as compared to the younger counterparts (42.5 % vs 17.2 %). The prevalence of myopia was 15.5 % among the urban students as compared to 8.2 % among the rural ones (RR = 1.89, 95 % CI = 1.1-3.24). The hypermetropia was more common in urban students than in rural ones (6.4 %) vs 5.9 %, RR = 1.08 (95 % CI: 0.52-2.24). Conclusion: The prevalence of refractive error in the school children of Nepal is 19.8 %. The students from urban settings are more likely to have refractive error than their rural counterparts. DOI: 10.3126/nepjoph.v2i2.3717 Nep J Oph 2010;2(2) 114-120